Этюды для левой руки: [роман] / Марианна Гончарова - Гончарова Марианна Борисовна (ЭКСМО, 2011)
Экземпляры: ф. 20 (20150210) / Инвентарный номер: 49550 / Цена: 105.00 / Авт.знак: Г 65 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-4